A shared enhancer controls a temporal switch between promoters during Drosophila primary sex determination. - González, A.N.; Lu, H.; Erickson, J.W. (Proceedings of the National Academy of Sciences of the United States of America, 2008)
Sex-lethal (Sxl), the master regulatory gene of Drosophila somatic sex determination, is stably maintained in an on or an off state by autoregulatory control of Sxl premRNA processing. Establishment of the correct Sxl splicing pattern requires the coordinate regulation of two Sxl promoters. The first of these promoters, SxlPe, responds to the female dose of two X chromosomes to produce a pulse of Sxl protein that acts on the premRNA products from the second promoter, SxlPm, to establish the splicing loop. SxlPm is active in both sexes throughout most of development, but nothing is known about how SxlPm is expressed during the transition from X signal assessment to maintenance splicing. We found that SxlPm is activated earlier in females than in males in a range of Drosophila species, and that its expression overlaps briefly with that of SxlPe during the syncytial blastoderm stage. Activation of SxlPm depends on the scute, daughterless, and runt transcription factors, which communicate X chromosome dose to SxlPe, but is independent of the X signal element sisA and the maternal co-repressor groucho. We show that DNA sequences regulating the response of SxlPe to the X chromosome dose also control the sex-differential response of SxlPm. We propose that co-expression of Sxl protein and its premRNA substrate facilitates the transition from transcriptional to splicing control, and that delayed activation of SxlPm in males buffers against the inappropriate activation of Sxl by fluctuations in the strength of the X chromosome signal.